PRODUCTION, SIZE DISTRIBUTION, AND LENGTH WEIGHT RELATIONSHIP OF LOBSTER LANDED IN THE SOUTH COAST OF YOGYAKARTA, INDONESIA - Aisyah Aisyah; Setiya Triharyuni (Research Center for Fisheries, 2010)
Lobster is one of the most important fisheries export commodities. An increasing trend of annual production during 1999-2005 was occurred, however a decreasing trend during 2005-2007 was observed. lt is likely that the long lived and slow growing species group do not capable to balance the fishing pressure.